A Facile and Controllable Method to In Situ Synthesize Stable Hydrophobic Vaterite Particles. Issue 5 (25th March 2019) - Dang, Haichun; Xu, Zhaozan; Chen, Zishan; Wu, Weiling; Feng, Juan; Sun, Yiyi; Jin, Fengchi; Li, Jiang; Ge, Fan
Abstract: The applications of hydrophobic vaterite in various fields have been limited by its thermodynamic instability and complex preparation methods. A facile batch, green, rapid, and controllable method is proposed to prepare stable hydrophobic vaterite microparticles with the presence of stearic acid (SA) via in situ synthesis. A possible formation process of SA‐modified calcium carbonate (CaCO3 ) particles is proposed. Hydrophobic vaterite is prepared by mixing calcium chloride and sodium carbonate aqueous solutions in the presence of SA within 1 min by high shearing stirring. The hydrophobic vaterite particles show more uniform morphology and particle size than that without SA. Interestingly, the hydrophobic vaterite particles exhibit sumac‐fruit‐like morphology consisting of spherical nanoparticles. The hydrophobicity of CaCO3 particles is enhanced significantly by 1% SA addition. Vaterite is stabilized by SA and vaterite content in CaCO3 particles is significantly enhanced from 35% to 97% based on the analysis of X‐ray diffraction data. CaCO3 particles without SA translate into rhombohedron completely after 24 h of incubation, while the sumac‐fruit‐like morphology of hydrophobic vaterite particles shows no obvious change after 96 h of incubation. No obvious phase transformation of the hydrophobic vaterite particles is found after 72 h of incubation, indicating high stability of the hydrophobic vaterite. Abstract : Stable hydrophobic vaterite microparticles are successfully developed with a facile batch, green, rapid, and controllable method in the presence of stearic acid via high shearing stirring. The hydrophobic vaterite particles exhibiting sumac‐fruit‐like morphology consist of spherical nanoparticles and show good morphology stability without obvious change after 96 h of incubation.